HOTATE SCALLOP (MIZUHOPECTEN YESSOENSIS) FARMING USING MIMIZURI AT SUZUKI TOSHIHIKO TOYOURA COMPANY, HOKKAIDO, JAPAN - Burhanudin, Burhanudin; Mardika, Hanisya Putri Kania; Sujadi, Frentina Murti; Anjaini, Jefri (Directorate of Research and Community Service (DRPM), 2025)
Japan is an archipelagic country with numerous marine commodities of high economic value. One of the most popular marine products among the Japanese population is the Hotate scallop (Mizuhopecten yessoensis). Hotate scallops are a type of shellfish that thrive in low-temperature environments, with their natural habitat commonly found in the northern seas of Japan, particularly in Hokkaido. Suzuki Toshihiko Company, located in Toyoura, Hokkaido Prefecture, is one of the companies engaged in the Hotate scallop industry. This study was conducted to examine the Mimizuri cultivation technique used by Suzuki Toshihiko Company. The study are divided into 3 methods ; the first method include observation; the second active participation, and the third method interview to collect primary data, while secondary data were obtained from relevant literature. The Mimizuri technique is a method of cultivating Hotate scallops by attaching them to a rope and raising them in the open sea. This technique involves several stages, starting with seed collection, seed sorting, the mimizuri stage, and finally the large-scale harvesting stage